Compliance to medical advice among patients having non-communicable disease in Jamnagar, Gujarat - Bhagora, Hiren D; Unadkat, Sumit V.; Parmar, Dipesh V (Indian Journal of Community Health, 2018)
Background: The low compliance by patients with non-communicable diseases to treatment and medical advice is a major therapeutic challenge. WHO study estimates that only 50% of patients suffering from chronic diseases in developed countries follow treatment recommendations. Aims & Objective: To estimate compliance to medical advice among patients with non-communicable diseases and to find out association between various socio-demographic factors and compliance to medical advice. Materials & Methods: It was a community based cross sectional study. Total 450 subjects (225 each from Urban and rural areas of the district) were studied using pre-tested and semi-structured questionnaire. Result: Medicines were taken as prescribed by 71.78% participants. Dose was missed on previous day and once in previous week by 26% and 35.78% participants respectively. Adherence to medical advice was found among 43.33% participants. Proportion of adherence was significantly low among participants more than 50 years of age (38.40%), among males (35.74%), among financially dependent (39.30%) and those having disease since 6years or more (36.92%). Conclusion: Large number of study subjects were found to be non-compliant to medical advice and also the compliance was lower in participants more than 50 years of age, among males and among those who were financially dependent. These risk groups may be targeted through counselling or health education sessions to increase compliance.